Strength distribution and fracture analyses of LiNbO3 and LiTaO3 single crystals under biaxial loading. Issue 14 (November 2017) - Gruber, M.; Kraleva, I.; Supancic, P.; Bielen, J.; Kiener, D.; Bermejo, R.
Abstract: The strength distribution and fracture behaviour of miniaturized Lithium niobate (LiNbO3 ) and Lithium tantalate (LiTaO3 ) single crystals were assessed under biaxial bending. The susceptibility of these materials to environmental assisted cracking (SCCG) was studied by means of constant cross-head displacement rate experiments in air and in water. Two different sample sizes were tested and compared to assess the Weibull volume effect. Experimental results showed a significant difference in strength, LiNbO3 being weaker than LiTaO3 . No apparent SCCG and no volume effect on strength were found. A different distribution to Weibull behaviour was observed in LiNbO3 . Fractography showed differences in the fracture patterns, due to the different cutting orientation of the two investigated materials with respect to the loading plane. New cleavage planes were identified as 10.1 for LiNbO3 and 1 2 ¯ .3 for LiTaO3 . Fracture surfaces of LiNbO3 revealed surface damage, which may be responsible for the lower strength compared to LiTaO3 .